2-(2-{[2-(4-Pyridylcarbonyl)hydrazinylidene]methyl}phenoxy)acetic acid - Xia, Jin Hong (International Union of Crystallography, 2010)
In the title compound, C(15)H(13)N(3)O(4), the pyridine and benzene rings are nearly perpendicular [dihedral angle = 84.24 (5)°]. In the crystal structure, classical O—H⋯N hydrogen bonding between the OH group of the carboxyl unit and a neighbouring pyridine ring N atom and N—H⋯O hydrogen bonding between the imine NH group and a neighbouring O atom of an acyl unit, together with complementary non-classical C—H⋯O hydrogen bonds between carboxyl O atoms and neighbouring CH groups, link the molecules into a three-dimensional system.